Impact of Prone Position on 12-Lead Electrocardiogram in Healthy Adults: A Comparison Study with Standard Electrocardiogram - Yunis Daralammouri; Murad Azamtta; Hamza Hamayel; Amro Adas; Osama Sawalmeh; Yahia Ismail; Saed H. Zyoud (Cardiology Research and Practice)
Background. The standard electrocardiogram (ECG) is commonly performed in the supine posture. It may be difficult to report ECG in a supine posture for those who are unable to adopt the supine posture because of certain circumstances such as acute respiratory distress syndrome—patients who are placed in a prone position for long periods to improve oxygenation. Few data are available on the impact of the prone position on the ECG recording with electrodes on the posterior chest. Examining and analyzing the type and extent of changes observed in the prone ECG in healthy adults have become vitally valuable. Methods. A cross-sectional observational study enrolled forty healthy adults (24 males and 16 females) aged between 18 and 40 years. The ECG was performed in two different body positions, supine and prone. Influence of prone position on the heart rate, mean QRS axis, amplitude, morphology, duration, mean T wave axis and polarity, mean P wave axis, PR, and mean QTc duration was evaluated. Results. The mean heart rate was higher in the prone position (73.2 ± 12.4 bpm) compared with the supine position (69.5 ± 11.5 bpm, p = 0.03). The QRS duration decreased considerably from supine (92.8 ± 12.6 ms) to prone (84.9 ± 11.9 ms, p<0.001). The mean QRS axis moved to the left in the prone posture (40.5° ± 32°) relative to the supine (49° ± 28°, p=0.015). The QRS amplitude in the precordial leads was significantly decreased from supine (7.42 ± 3.1 mV) to prone (3.68 ± 1.7 mV, p<0.001). In addition, changes in the QRS morphology in leads V1–V3 with the appearance of new Q waves were noted. A notable variation in the mean corrected QT (QTc) period with decrease in duration in prone posture ECG (385 ± 64.8) relative to supine (406 ± 18.8, p=0.05). Conclusions. Prone position ECG resulted in significant changes in healthy adults that should be aware of this as this can affect diagnosis and management strategies. Further studies are needed to investigate the impact of prone position on ECG recording in patients with cardiovascular diseases.